M-HOF material, preparation method thereof and application of M-HOF material in hydroxyl ion recognition

By preparing metal hydrogen bonded organic frame material (M-HOF) with layered aggregation structure, the problems of long detection time, inesistence and poor accuracy in the existing OH-detection methods are solved, and the hydroxide ions are achieved. Efficient identification and stability identification have expanded the application scope of M-HOF materials.

CN119144004AActive Publication Date: 2024-12-17LANZHOU UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411097374.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2024-12-17
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

The existing OH-detection methods have problems such as long detection time, inseparable interference resistance and poor accuracy, especially the lack of recognition ability of hydroxide ions.

Method used

Using a preparation method of metal hydrogen bonded organic frame material (M-HOF), compounds such as 4-(N-hydroxyforminamidine) benzoate, isonicotinic chloride hydrochloride, triethylamine and inorganic base are carried out. The reaction is formed to form an M-HOF material with a layered aggregation structure, and the hydroxide ions are identified by ultraviolet-visible absorption spectroscopy detection.

Benefits of technology

The M-HOF material exhibits good stability and anti-interference ability under different pH conditions, can effectively identify hydroxide ions, expand the application range of M-HOF material, and displays good linearity and accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144004A_ABST
    Figure CN119144004A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metal hydrogen bond organic frameworks, and discloses an M-HOF material, a preparation method thereof and application of the M-HOF material in hydroxyl ion recognition. The preparation method of the M-HOF material comprises the following steps: mixing 4-(N-hydroxyformamidine) methyl benzoate, isonicotinoyl chloride hydrochloride, triethylamine and acetonitrile, and carrying out a first reaction to obtain an intermediate product; mixing the intermediate product, lithium hydroxide, methanol and water, carrying out a second reaction, and adjusting the pH value of the obtained product to be less than or equal to 1 after the second reaction is finished, so as to obtain a pyridine-carboxylic acid ligand; and mixing the pyridine-carboxylic acid ligand, zinc nitrate hexahydrate, N, N-dimethylformamide and water, and carrying out a third reaction to obtain the M-HOF material. The M-HOF material has a layered aggregation structure and has good stability in aqueous solutions with different pH values, and the aqueous phase stability of the M-HOF material lays a solid foundation for future application research of the M-HOF material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal hydrogen bond organic framework, and in particular to an M-HOF material and a preparation method thereof and application in hydroxide ion recognition. Background Art

[0002] The biggest difference between metal hydrogen-bonded organic frameworks (M-HOFs) and MOFs is that the structure of M-HOFs is constructed by hydrogen bonds between complex molecules. The inherent hydrogen bonding interactions in its structure make M-HOFs have research potential in many fields including gas adsorption, sensing detection, and proton conduction. However, due to the difficulties in the design and control of M-HOF structures, compared with mature systems such as MOFs and COFs, research on them is still in its infancy. Therefore, the study of new M-HOF materials is also of certain significance for expanding the scope and depth of M-HOF research.

[0003] Hydroxide is one of the most widely used basic chemical products and is widely used in industry. Soluble hydroxides can cause a series of serious harms to life and even the entire ecological environment by increasing the pH of the solution. Therefore, in many cases in production and life, it is necessary to - There are a series of methods to detect OH-, such as titration, colorimetry or electrochemical method. However, these methods often have problems such as long detection time, intolerant to interference or poor accuracy. Therefore, it is necessary to design a new OH - Sensing materials. A variety of materials that can be used for OH have been developed in current research. – However, due to the defects of some MOFs in terms of stability, response range, and anti-interference ability, it is necessary to continue to develop new stable and anti-interference OH - Sensing materials. Summary of the invention

[0004] The purpose of the present invention is to provide an M-HOF material and a preparation method thereof and an application thereof in hydroxyl ion identification, so as to solve the existing detection of OH - Problems include long detection time, intolerance to interference and poor accuracy.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing an M-HOF material, comprising the following steps:

[0007] Mixing methyl 4-(N-hydroxycarboxamidine)benzoate, isonicotinoyl chloride hydrochloride, triethylamine and a first solvent, and performing a first reaction to obtain an intermediate product;

[0008] The intermediate product, the inorganic base and the second solvent are mixed to carry out a second reaction, and after the second reaction, the pH of the obtained product is adjusted to ≤ 1 to obtain a pyridine-carboxylic acid ligand;

[0009] The pyridine-carboxylic acid ligand, zinc nitrate, N,N-dimethylformamide and water are mixed and subjected to a third reaction to obtain an M-HOF material.

[0010] Preferably, in the above-mentioned method for preparing an M-HOF material, the molar ratio of methyl 4-(N-hydroxycarboxamidine)benzoate, isonicotinoyl chloride hydrochloride and triethylamine is 1-2:1-2:1-6;

[0011] The usage ratio of the triethylamine and the first solvent is 0.5-2 mol:1L;

[0012] The first solvent is acetonitrile.

[0013] Preferably, in the above-mentioned method for preparing an M-HOF material, the conditions of the first reaction are: the atmosphere is argon, the temperature is 50-100° C., and the time is 6-18 hours.

[0014] Preferably, in the above-mentioned method for preparing an M-HOF material, the molar ratio of the intermediate product to the inorganic base is 1:1 to 5;

[0015] The inorganic base is lithium hydroxide, sodium hydroxide or potassium hydroxide;

[0016] The mass ratio of the intermediate product to the volume of the second solvent is 1-2 g: 15-50 mL;

[0017] The second solvent is a mixed solution of an alcohol substance and water;

[0018] The volume ratio of the alcohol substance to water in the second solvent is 1-3:1-3.

[0019] Preferably, in the above-mentioned method for preparing an M-HOF material, the temperature of the second reaction is 85 to 95° C., and the time of the second reaction is 8 to 16 hours.

[0020] Preferably, in the above-mentioned method for preparing an M-HOF material, the molar ratio of the pyridine-carboxylic acid ligand to zinc nitrate is 1:0.5-2;

[0021] The usage ratio of the pyridine-carboxylic acid ligand, N,N-dimethylformamide and water is 0.2-1.8 mmol:10 mL:30-50 mL.

[0022] Preferably, in the above-mentioned method for preparing an M-HOF material, the temperature of the third reaction is 80 to 120° C., and the time of the third reaction is 48 to 240 hours.

[0023] The present invention also provides an M-HOF material prepared by the method for preparing the M-HOF material.

[0024] The present invention also provides an application of an M-HOF material in hydroxide ion recognition.

[0025] Preferably, in the application of the above-mentioned M-HOF material in hydroxide ion recognition, the application method comprises the following steps:

[0026] The M-HOF material is mixed with water to obtain a suspension; the suspension is then mixed with a hydroxide ion aqueous solution to obtain a mixed solution, and the mixed solution is subjected to UV-visible absorption spectrum detection.

[0027] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0028] The M-HOF material of the present invention has a layered aggregation structure and has good stability in aqueous solutions of different pH values. Its aqueous phase stability lays a solid foundation for its future application research. The principle of the UV-visible recognition of hydroxide ions by the M-HOF material of the present invention is to destroy the hydrogen bond interaction in the material and release charged small molecules through the hydrogen extraction effect of hydroxide ions, and to achieve recognition of hydroxide ions by gradual dissociation from the outside to the inside. The material can be used to identify hydroxide ions, expanding the application range of the M-HOF material; and under the current recognition conditions, the material has good recognition linearity for hydroxide ions; at the same time, the material has good anti-interference ability for the recognition of hydroxide ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.

[0030] Figure 1 is a single molecule structure diagram of the M-HOF material of Example 1;

[0031] Figure 2 It is a layered aggregation stacking diagram of the M-HOF material of Example 1;

[0032] Figure 3 is a thermal analysis diagram of the M-HOF material of Example 1;

[0033] Figure 4 This is the XRD pattern of the M-HOF material of Example 1 immersed in aqueous solutions with different pH values ​​for 3d.

[0034] Figure 5 The UV-visible identification result of the M-HOF material of Example 1 to sodium hydroxide;

[0035] Figure 6 The UV-visible identification result of the M-HOF material of Example 1 to potassium hydroxide;

[0036] Figure 7 The UV-visible identification result of the M-HOF material of Example 1 to lithium hydroxide;

[0037] Figure 8 This is the UV-visible identification result of the M-HOF material in Example 1 to barium hydroxide. DETAILED DESCRIPTION

[0038] The invention provides a method for preparing an M-HOF material, comprising the following steps:

[0039] Mixing methyl 4-(N-hydroxycarboxamidine)benzoate, isonicotinoyl chloride hydrochloride, triethylamine and a first solvent, and performing a first reaction to obtain an intermediate product;

[0040] The intermediate product, the inorganic base and the second solvent are mixed to carry out a second reaction, and after the second reaction, the pH of the obtained product is adjusted to ≤ 1 to obtain a pyridine-carboxylic acid ligand;

[0041] The pyridine-carboxylic acid ligand, zinc nitrate, N,N-dimethylformamide and water are mixed and subjected to a third reaction to obtain an M-HOF material.

[0042] In the present invention, the specific process of mixing methyl 4-(N-hydroxycarboxamidine)benzoate, isonicotinoyl chloride hydrochloride, triethylamine and the first solvent is as follows:

[0043] First, methyl 4-(N-hydroxyformamidine)benzoate, triethylamine and a first solvent are mixed, and then isonicotinoyl chloride hydrochloride is added in batches and mixed;

[0044] There is no special limit on the number of times of adding in batches, and no spraying is required during the adding in batches.

[0045] In the present invention, the CAS number of the methyl 4-(N-hydroxycarboxamidine)benzoate is 184778-33-4.

[0046] In the present invention, the molar ratio of methyl 4-(N-hydroxycarboxamidine)benzoate, isonicotinoyl chloride hydrochloride and triethylamine is preferably 1-2:1-2:1-6, more preferably 1-1.7:1-1.7:2-5, and more preferably 1:1:3.

[0047] In the present invention, the usage ratio of the triethylamine to the first solvent is preferably 0.5-2 mol:1L, more preferably 1-1.5 mol:1L, and more preferably 1.2 mol:1L.

[0048] In the present invention, the first solvent is preferably acetonitrile.

[0049] In the present invention, the conditions of the first reaction are: the atmosphere is preferably argon; the temperature is preferably 50-100°C, more preferably 70-90°C, more preferably 85°C; the time is preferably 6-18h, more preferably 8-16h, more preferably 12h.

[0050] In the present invention, after the first reaction is completed, the process further comprises: mixing the product with a saturated NaHCO3 solution to quench the reaction, and then extracting, drying and purifying;

[0051] The usage ratio of saturated NaHCO3 solution to methyl 4-(N-hydroxycarboxamidine)benzoate is preferably 1-2.5 L: 1-2 mol, more preferably 1.25-2 L: 1-1.7 mol, and more preferably 1.5 L: 1 mol;

[0052] The extractant in the extraction is preferably dichloromethane;

[0053] The desiccant in the drying is preferably anhydrous Na2SO4;

[0054] The purification method is preferably silica gel column purification;

[0055] The eluent in the purification is preferably a mixture of petroleum ether and ethyl acetate, and the volume ratio of petroleum ether to ethyl acetate is preferably 4:1.

[0056] In the present invention, the specific process of mixing the intermediate product, the inorganic base and the second solvent is:

[0057] The intermediate product is mixed with a second solvent and then an inorganic base is added.

[0058] In the present invention, the molar ratio of the intermediate product to the inorganic base is preferably 1:1-5, more preferably 1:1-2, and more preferably 1:1.25.

[0059] In the present invention, the inorganic base is preferably lithium hydroxide, sodium hydroxide or potassium hydroxide, more preferably lithium hydroxide or sodium hydroxide, and more preferably lithium hydroxide;

[0060] The lithium hydroxide is preferably lithium hydroxide monohydrate.

[0061] In the present invention, the volume ratio of the mass of the intermediate product to the second solvent is preferably 1-2 g:15-50 mL, more preferably 1.2-1.6 g:20-40 mL, and more preferably 1.4 g:30 mL.

[0062] In the present invention, the second solvent is preferably a mixed solution of an alcohol substance and water;

[0063] The alcohol substance is preferably methanol or ethanol, more preferably methanol.

[0064] In the present invention, the volume ratio of the alcohol substance to water in the second solvent is preferably 1-3:1-3, more preferably 1-2.5:1-2.5, and more preferably 1:1.

[0065] In the present invention, the temperature of the second reaction is preferably 85-95°C, more preferably 82-87°C, and more preferably 85°C; the time of the second reaction is preferably 8-16h, more preferably 10-14h, and more preferably 12h.

[0066] In the present invention, the pH of the obtained product is adjusted to ≤ 1 preferably by using hydrochloric acid.

[0067] In the present invention, after adjusting the pH of the obtained product to ≤1, the method further comprises: performing vacuum rotary evaporation to obtain the product, filtering the product, and washing and drying the filter cake obtained by filtration;

[0068] The washing detergent is water.

[0069] In the present invention, the structure of the pyridine-carboxylic acid ligand is as shown in Formula 1,

[0070]

[0071] In the present invention, the molar ratio of the pyridine-carboxylic acid ligand to zinc nitrate is preferably 1:0.5-2, more preferably 1:0.7-1.5, and even more preferably 1:1.

[0072] The usage ratio of the pyridine-carboxylic acid ligand, N,N-dimethylformamide and water is 0.2-1.8 mmol:10 mL:30-50 mL, more preferably 0.5-1.5 mmol:10 mL:35-45 mL, and more preferably 1 mmol:10 mL:40 mL.

[0073] In the present invention, the zinc nitrate is preferably zinc nitrate hexahydrate.

[0074] In the present invention, the temperature of the third reaction is preferably 80-120°C, more preferably 85-100°C, and more preferably 90°C; the time of the third reaction is preferably 48-240h, more preferably 72-192h, and more preferably 120h.

[0075] In the present invention, after the third reaction is completed, the method further comprises: filtering the obtained product, washing and drying the obtained filter cake;

[0076] The washing agent is preferably methanol.

[0077] The present invention also provides an M-HOF material prepared by the method for preparing the M-HOF material.

[0078] In the present invention, in the M-HOF material, the inorganic metal center is a zinc ion, and the organic ligand is a pyridine-carboxylic acid ligand; the zinc ion is hexacoordinated, including two nitrogen atoms from the pyridine-carboxylic acid ligand and four oxygen atoms from coordinated water molecules; the pyridine in the pyridine-carboxylic acid ligand structure coordinates with the zinc ion, and the carboxylic acid group remains exposed, and then interacts with π-π through intermolecular hydrogen bonds to form a three-dimensional network structure.

[0079] The present invention also provides an application of an M-HOF material in hydroxide ion recognition.

[0080] Preferably, in the application of the above-mentioned M-HOF material in hydroxide ion recognition, the application method comprises the following steps:

[0081] The M-HOF material is mixed with water to obtain a suspension; the suspension is then mixed with a hydroxide ion aqueous solution to obtain a mixed solution, and the mixed solution is subjected to UV-visible absorption spectrum detection.

[0082] In the present invention, the concentration of the M-HOF material in the suspension is preferably 0.05-1 g / L, more preferably 0.1-0.5 g / L, and more preferably 0.2 g / L.

[0083] In the present invention, after the M-HOF material is mixed with water, the steps further include: ultrasonication and sedimentation;

[0084] The ultrasonic time is preferably 0.5 to 2 hours, more preferably 0.7 to 1.5 hours, and more preferably 1 hour;

[0085] The sedimentation time is preferably 0.5 to 2 hours, more preferably 0.7 to 1.5 hours, and more preferably 1 hour.

[0086] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0087] Example 1

[0088] A method for preparing an M-HOF material comprises the following steps:

[0089] Under argon protection, methyl 4-(N-hydroxycarboxamidine)benzoate (3.8838 g, 0.02 mol), triethylamine (8.340 mL, 0.06 mol) and anhydrous acetonitrile (50 mL) were uniformly mixed; isonicotinoyl chloride hydrochloride (3.5602 g, 0.02 mol) was then added in batches; after the addition was completed, the reaction was stirred at 85°C for 12 h to obtain a light yellow solid-liquid mixture; after adding 30 mL of saturated NaHCO3 solution to quench the reaction, the yellow organic phase was separated by extraction with dichloromethane, the organic phase was dried with anhydrous Na2SO4 and then spin-dried, and then purified by silica gel column (the eluent was petroleum ether and ethyl acetate in a volume ratio of 4:1) to obtain an intermediate product (5.2501 g, yield: 93.3%);

[0090] The intermediate product (1.4064 g, 5 mmol) was dissolved in a mixed solution of methanol (15 mL) and deionized water (15 mL), and then lithium hydroxide monohydrate (0.2622 g, 6.25 mmol) was added and mixed evenly, and heated to 85°C for 12 h. After the reaction, hydrochloric acid was used to adjust the pH to ≤ 1, and the product was obtained by vacuum rotary evaporation, which was then filtered, and the filter cake was washed with water for 3 times, and then dried to obtain a pyridine-carboxylic acid ligand (1.2974 g, yield 97.1%);

[0091] The preparation of the above pyridine-carboxylic acid ligand is as follows:

[0092]

[0093] Pyridine-carboxylic acid ligand (26.7 mg, 0.1 mmol), zinc nitrate hexahydrate (29.7 mg, 0.1 mmol), N,N-dimethylformamide (1 mL) and deionized water (4 mL) were fully mixed and heated to 90°C for 120 h. After the reaction, the product was filtered and the filter cake was washed 5 times with methanol and then dried to obtain M-HOF material (28.5 mg, yield 42%).

[0094] The crystal structure data of the M-HOF material prepared in Example 1 is shown in Table 1.

[0095] Table 1 Crystal structure data of M-HOF material in Example 1

[0096]

[0097]

[0098] The single molecule structure diagram and layered aggregation stacking diagram of the M-HOF material prepared in Example 1 are shown in FIG. Figure 1 and 2 As shown. Figure 1 and 2It can be seen that the zinc ion in the M-HOF material is hexacoordinated, containing two nitrogen atoms from the pyridine-carboxylic acid ligand and four oxygen atoms from the coordinated water molecules; the M-HOF material has a layered aggregation structure, and through intermolecular hydrogen bonds and π-π interactions, it forms a three-dimensional stacking structure.

[0099] The M-HOF material prepared in Example 1 was subjected to thermal analysis and XRD test after being immersed in aqueous solutions of different pH values ​​for 3 days. The results are as follows: Figure 3 and 4 As shown. Figure 3 and 4 It can be seen that the M-HOF material has good stability below 120°C and has good stability in a wide pH range.

[0100] Example 2

[0101] An application of an M-HOF material in identifying hydroxide ions comprises the following steps:

[0102] The M-HOF material prepared in Example 1 was ground and added with deionized water to prepare a 0.2 g / L solution, followed by ultrasonic treatment for 1 h and sedimentation for 1 h to obtain a stable suspension.

[0103] Add 0 to 20 μL of 0.05 mol / L sodium hydroxide aqueous solution to 2 mL of the stable suspension and detect the changes in its UV-visible absorption spectrum. The results are as follows: Figure 5 shown.

[0104] Depend on Figure 5 It can be seen that the absorption peak of the M-HOF suspension at 249nm gradually increases and the absorption peak at 306nm gradually decreases. The detection working electrode of the M-HOF material has a good recognition effect on sodium hydroxide. According to the calculation, the recognized R 2 =0.98872.

[0105] Example 3

[0106] An application of an M-HOF material in identifying hydroxide ions is consistent with that in Example 2, except that sodium hydroxide is replaced by potassium hydroxide.

[0107] The UV-visible absorption test results of the M-HOF material for potassium hydroxide in Example 1 are as follows: Figure 6 As shown. Figure 6 It can be seen that the detection working electrode of M-HOF material has a good recognition effect on potassium hydroxide. According to the calculation, the recognized R 2 =0.97818.

[0108] Example 4

[0109] An application of an M-HOF material in identifying hydroxide ions is consistent with that in Example 2, except that sodium hydroxide is replaced by lithium hydroxide.

[0110] The UV-visible absorption test results of the M-HOF material for lithium hydroxide in Example 1 are as follows: Figure 7 As shown. Figure 7 It can be seen that the detection working electrode of M-HOF material has a good recognition effect on lithium hydroxide. According to calculation, the recognized R 2 =0.98378.

[0111] Example 5

[0112] An application of an M-HOF material in identifying hydroxide ions is consistent with that in Example 2, except that sodium hydroxide is replaced by barium hydroxide, and the concentration of the barium hydroxide aqueous solution is 0.025 mol / L.

[0113] The UV-visible absorption test results of the M-HOF material for barium hydroxide in Example 1 are as follows: Figure 8 As shown. Figure 8 It can be seen that the detection working electrode of M-HOF material has a good recognition effect on barium hydroxide. According to calculation, the recognized R 2 =0.98677.

[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an M-HOF material, characterized in that: The following steps are involved: Mixing methyl 4-(N-hydroxycarboxamidine)benzoate, isonicotinoyl chloride hydrochloride, triethylamine and a first solvent, and performing a first reaction to obtain an intermediate product; The intermediate product, the inorganic base and the second solvent are mixed to carry out a second reaction, and after the second reaction, the pH of the obtained product is adjusted to ≤ 1 to obtain a pyridine-carboxylic acid ligand; The pyridine-carboxylic acid ligand, zinc nitrate, N,N-dimethylformamide and water are mixed and subjected to a third reaction to obtain an M-HOF material.

2. The method for preparing the M-HOF material according to claim 1, characterized in that: The molar ratio of methyl 4-(N-hydroxycarboxamidine)benzoate, isonicotinoyl chloride hydrochloride and triethylamine is 1-2:1-2:1-6; The usage ratio of the triethylamine and the first solvent is 0.5-2 mol:1L; The first solvent is acetonitrile.

3. The method for preparing the M-HOF material according to claim 2, characterized in that: The conditions of the first reaction are: atmosphere is argon, temperature is 50-100° C., and time is 6-18 hours.

4. The method for preparing the M-HOF material according to claim 3, characterized in that: The molar ratio of the intermediate product to the inorganic base is 1:1-5; The inorganic base is lithium hydroxide, sodium hydroxide or potassium hydroxide; The mass ratio of the intermediate product to the volume of the second solvent is 1-2 g: 15-50 mL; The second solvent is a mixed solution of an alcohol substance and water; The volume ratio of the alcohol substance to water in the second solvent is 1-3:1-3.

5. The method for preparing the M-HOF material according to claim 4, characterized in that: The temperature of the second reaction is 85-95° C., and the time of the second reaction is 8-16 hours.

6. The method for preparing the M-HOF material according to claim 4 or 5, characterized in that: The molar ratio of the pyridine-carboxylic acid ligand to zinc nitrate is 1:0.5-2; The usage ratio of the pyridine-carboxylic acid ligand, N,N-dimethylformamide and water is 0.2-1.8 mmol:10 mL:30-50 mL.

7. The method for preparing the M-HOF material according to claim 6, characterized in that: The temperature of the third reaction is 80-120° C., and the time of the third reaction is 48-240 hours.

8. The M-HOF material obtained by the method for preparing the M-HOF material according to any one of claims 1 to 7.

9. Use of the M-HOF material according to claim 8 in hydroxide ion recognition.

10. The use of the M-HOF material according to claim 9 in hydroxide ion recognition, characterized in that: The application method comprises the following steps: The M-HOF material is mixed with water to obtain a suspension; the suspension is then mixed with a hydroxide ion aqueous solution to obtain a mixed solution, and the mixed solution is subjected to UV-visible absorption spectrum detection.

Citation Information

Patent Citations

  • Zinc coordination polymer based on pyrazole carboxylic acid ligand, preparation method and application

    CN115340680A

  • Hydrogen bond organic framework material as well as preparation method and application thereof

    CN118146526A

  • Compounds for nonsense suppression, and methods for their use

    US20170204073A1

  • Water stable zinc-based metal organic framework and method of use

    US20200190114A1

  • Metal-organic frameworks for the removal of nitrate from aqueous solutions

    WO2023245215A1